2016
DOI: 10.2196/jmir.5832
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Surfing on Social Health Networks is Associated With Increased Knowledge and Patient Health Activation

Abstract: BackgroundThe advent of the Internet has driven a technological revolution that has changed our lives. As part of this phenomenon, social networks have attained a prominent role in health care. A variety of medical services is provided over the Internet, including home monitoring, interactive communications between the patient and service providers, and social support, among others. This study emphasizes some of the practical implications of Web-based health social networks for patients and for health care sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 35 publications
4
62
0
Order By: Relevance
“…, Jeong‐Nam & Seungyoon , Grosberg et al . ). Computer‐mediated medical information empowers health consumers to make informed decisions for their healthcare by presenting them different treatment options (Seckin ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Jeong‐Nam & Seungyoon , Grosberg et al . ). Computer‐mediated medical information empowers health consumers to make informed decisions for their healthcare by presenting them different treatment options (Seckin ).…”
Section: Discussionmentioning
confidence: 97%
“…The potential of digital communication is still underestimated by healthcare professionals. Online health communities can be used to share experiences, exchange knowledge, increase disease-specific expertise, reduce disease burden, enable interdisciplinary collaboration, engage patients in their healthcare process and to tailor care to their individual needs (Christensen & Hickie 2010, Wicks et al 2010, Van der Eijk et al 2013, Jeong-Nam & Seungyoon 2014, Grosberg et al 2016. Computer-mediated medical information empowers health consumers to make informed decisions for their healthcare by presenting them different treatment options (Seckin 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that participation in online social health networks increased medical knowledge and empowered patients. 6 Additionally, engagement with web-based interventions can impact patient decisions such as alcohol abstinence and are being tested for encouraging a heart healthy lifestyle. 9,10 The men with USD in our study often expressed that hearing from other men with similar experiences was helpful and were grateful for the responses.…”
Section: Discussionmentioning
confidence: 99%
“…2 In prior qualitative analyses of online health forums for patients with chronic cough, breast and prostate cancer, and vasectomy, researchers concluded that the online community generally provided patients with beneficial support and information. [3][4][5][6] Genitourinary disease is especially suitable for online interaction, given that relative anonymity may reduce any potential embarrassment when discussing sensitive issues.…”
mentioning
confidence: 99%
“…Healthcare privacy concerns are also prominent (Iyengar, Kundu, and Pallis ; Robichau ). Interventions to increase engagement may shift social norms about appropriate patient behavior (Hibbard and Greene ), particularly when focused on patient‐to‐patient interaction (Grosberg et al ). Having consumers interact with each other online also increases engagement (Lorig et al ), making for a promising method to improve FWB.…”
Section: Applications Of the Hfwb Framework In Healthcare Exchangementioning
confidence: 99%